A dynamic ultrasonic emitter inspired by horseshoe bat noseleaves. (29th April 2016) - Fu, Yanqing; Caspers, Philip; Müller, Rolf
Abstract: The emission of biosonar pulses in horseshoe bats (family Rhinolophidae) differs from technical sonar in that it has dynamic features at the interface to the free field. When the horseshoe bats emit their biosonar pulses through the nostrils, the walls of a horn-shaped baffle (anterior leaf) are in motion while diffracting the outgoing ultrasonic wave packets. Here, biomimetic reproductions of the dynamic emission shapes of horseshoe bats have been studied for their ability to impose time-variant signatures onto the outgoing pulses. It was found that an elliptical sound outlet with rotating baffles that were attached along the direction of the major axis can be well suited for this purpose. Most importantly, concave baffle shapes were found to produce strongly time-dependent devices characteristics that could reach a root-mean-square-difference between beampatterns of almost 6 dB within a rotation angle of 10°. In contrast to this, a straight baffle shape needs to be rotated over 60° for a similar result. When continuously rotated in synchrony with the emitted pulses, the concave biomimetic baffles produced time-variant device characteristics that depended jointly on direction, frequency, and time. Since such device properties are so easily produced, it appears well worthwhile to explore their use in engineering.